Ultra-broadband metamaterial perfect solar absorber with polarization-independent and large incident angle-insensitive. (December 2022) - Zhou, Zhangkun; Chen, Yan; Tian, Yonghong; Liang, Jian; Yang, Wenxing
Highlights: 1. The metamaterial solar absorber can achieve 97.6% average absorption from 400 to 2500 nm. 2. The absorber with a simple structure and low cost. 3. The absorber is polarization-independent and large incident angle-insensitive. Abstract: Broadband metamaterial perfect absorbers have attracted a great attention to the people who study its use in solar energy harvesting. However, it is an extremely challenge to integrate such properties as ultra-broadband, perfect absorption, polarization-independent, angle-insensitive to a large incident angle and so on into a simple absorber structure. In this paper, we use FDTD to design a simple ultra-broadband metamaterial perfect absorber, consisting of x-cavity titanium nano-disk array based on a Silicon nitride-Titanium-Silicon nitride-Titanium four-layer structure. The optimized results indicate that the absorber broadband absorption spectra range from 400 nm to 2500 nm with 97.6% average absorption at normal incidence. The interactions among SPR, MR and CR lead to a high absorption. Moreover, the absorber is both polarization-independent and large incident angle-insensitive for both TE and TM-polarized waves. In addition, the absorber has an extremely high tolerance to fabrication errors, which is of great significance for practical production and application.